Dyeing of Jute Fabric with Natural Colorants Extracted from Green Turmeric: A Green Approach of Jute Dyeing in Cottage Industry (Journal of Science and Technology Research, 2026)
Synthetic dyes conquered the natural colorants due to its outstanding properties of color  matching, high clarities, better serviceability and ease of processing despite its adverse  effect on environment. Jute fiber, the golden fiber of Bangladesh, is commercially dyed  with hazardous synthetic dyes especially using basic dyes, which plays an adverse role  on the environment. To overcome this issue, an attempt is made to apply an ecofriendly  natural colorant extracted from green turmeric for the jute fabric to boost up the  sustainable and cleaner wet processing of our golden fibre. In this study, the potentials of  natural colorants extraction from green turmeric and consequent dyeing are evaluated.  Natural colorants were extracted by facile boiling of green turmeric paste at 100℃ for  60 minutes in aqueous, acidic and alkaline media. The solid residues were then separated  from the solution with the nylon strainer. Subsequently, scoured and bleached jute  fabrics were dyed with the extracted colorants in exhaust dyeing method. To investigate  the effects of different synthetic mordants, mordanting of jute fabric were done with  potash-alum, tannic acid, ferrous-(II) sulfate heptahydrate, stannous-(II) chloride  pentahydrate, potassium dichromate, and copper-(II) sulfate pentahydrate. The impacts  of temperature, dyebath pH, mordants, and dyeing period were intensively observed to  get optimum dyeing conditions. The impact of dyeing parameters was evaluated in terms  of color strength (k/s value) and chromaticity of the dyed fabric. The results revealed  that different mordants, temperature, pH and dyeing period showed significant effects  on the color strength and chromaticity. Potash-alum, tannic acid, and copper-(II) sulfate  pentahydrate mordanted jute fabrics exhibited good color fastness to wash with a grey  scale ratting of 3-4 to 4, while other showed poor color fastness to wash. J. of Sci. and Tech. Res. 6(2): 55-64, 2025